The Implementation of English Teaching Learning Process For Young Learnes In TK Harapan, Semampir Distric, Surabaya, Academic Year 2021/2022 - Aina, Intan Maulida Qorry’; Rozy, Fianico Sukmana (Journal of Early Childhood Education Studies, 2022)
The aim of this study was to describe the implementation of English learning in TK Harapan. This study applied the qualitative approach in form of a descriptive research. The data source was teacher, documents (weekly plan program, daily lesson plan, instruments for assessment, the students works, photos and videos. The data collection was conducted by interview, documentation, and observation. The data validity was conducted by applying the source and technique triangulations. The technique of data analysis was conducted by data reduction, data display, and verification. The result showed media used was flashcard, LCD, projector, and English textbook for Kindergarten.The methods of English teaching learning process applied were TPR (Total Physical Response), song, and game. The learning implementation was applied through composing the daily lesson plan which including five procedures namely before coming into class, opening activity, apperception activity, opening activity, main activity, and closing activity. The assessment was conducted by observation, check-list, and portfolio. The English learning for young learners was focussed on listening and speaking skills. Based on the data in this study, it could be assumed that the English teaching learning process in TK Harapan had worked well and it was able to develop the English ability of young learners.